Analysis of Evolution of Coupled Lorentz Resonances and Their Sensing Properties in Terahertz Metamaterials - Jiang, Nan; Zhang, Ziye; Liang, Wanlin; Deng, Yuwang; Zhang, Pujing; Zhang, Cunlin; Zhou, Qingli (Frontiers in Physics, 2022)
Combined with experimental and simulated results, the resonances and metamaterial induced transparency have been theoretically investigated using the Lorentz oscillator model for terahertz metamaterials with unequal-length bar structures. The bar spacing has an impact on the spectral evolution, implying the coupling between metal bars varies correspondingly in one unit cell and the adjacent cells. Different from the evidence that the strongest coupling occurs in double bar structures when the bar spacing is uniform in the entire sample, the coupling in three bar structures is more complicated due to the weakened coupling with the middle bar and increased coupling between other two bars by further increasing the bar spacing. The dependence of calculated transmission spectra on the damping rate and coupling coefficient is demonstrated, showing the fitting parameters could control and tune the resonant dips, the transparency peaks, and even the quality factors of the spectra regularly. Furthermore, the sensing properties have been investigated by simulating the spectral evolution with the overlayers of different refractive index to optimize the sensing parameters. Our obtained results could advance the understanding of resonance coupling and offer the possibility to further study the modulation and biosensing in the coupled terahertz devices.